2009
DOI: 10.1093/annonc/mdp368
|View full text |Cite
|
Sign up to set email alerts
|

Subdural collections arising from calvarial metastases following discontinuation of anti-angiogenic therapy

Abstract: letters to the editor Subdural collections arising from calvarial metastases following discontinuation of antiangiogenic therapyWe report two metastatic breast cancer patients with diffuse calvarial involvement who developed symptomatic subdural collections shortly after discontinuing anti-angiogenic therapy. The first patient had metastatic disease in the liver, skin, and bones, including the calvarium (Figure 1A), and developed subdural collections 3 weeks after discontinuing a 9-week course of sunitinib at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Skull metastasis demonstrates the same characteristic. In the past literatures, skull metastasis from stomach cancer demonstrates one of the least frequent incidences (15). The mechanism of the peculiar metastasis in these cases is difficult to elucidate.…”
Section: Discussionmentioning
confidence: 99%
“…Skull metastasis demonstrates the same characteristic. In the past literatures, skull metastasis from stomach cancer demonstrates one of the least frequent incidences (15). The mechanism of the peculiar metastasis in these cases is difficult to elucidate.…”
Section: Discussionmentioning
confidence: 99%
“…There was no discussion on the causal mechanism [8]. Wong et al [9] reported on two patients with metastatic breast cancer to the brain, one treated with bevacizumab and the other with sunitinib (a TK inhibitor that targets the vascular endothelial growth factor receptor). In both cases, the SDHs did not occur during therapy but after the discontinuation of therapy.…”
Section: Bevacizumabmentioning
confidence: 99%
“…In both cases, the SDHs did not occur during therapy but after the discontinuation of therapy. The authors postulated that cessation of the antiangiogenic chemotherapy led to a compensatory proangiogenic state that resulted in leakage from the capillaries and subsequent subdural collection [9].…”
Section: Bevacizumabmentioning
confidence: 99%
“…78 An alternative approach based on the combination of chemotherapy and angiogenesis inhibitors (e.g., anti cancer conjugated polymers or selenium) was found to be effective in treating osteosarcoma and bone metastases. [79][80][81] Clinical trials using this approach included a 30 kDa dual-targeted conjugate comprised of HPMA copolymer backbone, the potent anti-angio-genic agent TNP-470, and alendronate (ALN); the chemotherapy showed promise in treating osteosarcoma. 82 In other works, the issues of dose limiting neurotoxicity were overcome by employing caplostatin, an HPMA copolymer conjugate of TNP-470.…”
Section: Nanoscale Conjugated Copolymer Selenium and Liposome For Bon...mentioning
confidence: 99%